OFR-5-76 Development And Evaluation Of Radon Sealants For Uranium Mines ? Introduction - H. G. Hammon (The National Institute for Occupational Safety and Health (NIOSH), 1975)
Uranium miners have been shown to develop lung cancer in direct proportion to the time of exposure in the mine and the concentration of radioactivity (cumulative working level).1 Radon gas is continually evolved from the uranium ore, but because of its shoe half-life, 3.82 days, it is soon decomposed into particulate daughter products, which along with the dust in the mine, become deposited in the miners' lungs. At present, massive ventilation is the only effective method of reducing the radioactivity concentration in the mines. However, the Bureau of Mines is evaluating the possibility of using coatings on the mine wall that will have sufficiently low permeability to radon that the gas will decompose into the particulate daughter products before it can permeate the coating. Permanently trapped in the coating, the daughter products would be prevented from dispersing in the mine atmosphere. Lawrence Livermore Laboratory was asked to aid in this investigation. The direct determination of radon permeability is more difficult than that of the other noble gases because of the short half-life of the gas and radioactive contamination of the apparatus. We felt that it should be possible to estimate radon permeation coefficients from other noble gas permeation coefficients. It was noted that the log of the diffusion constants for helium, neon, argon, and krypton, as reported by Meares2,3 plotted to a straight line-against the square of-the gas molecularddia meter. The log of the permeation coefficients also plotted to a straight line against the square of the gas molecular diameter. Thus, by determining the permeation coefficients of such gases as argon and krypton through various films and coatings, it appeared likely that radon permeation coefficients could be estimated. In addition we felt it should be possible to find some relationship between polymer structure and he noble gas permeation coefficient that would aid in the selection of coatings materials as radon barriers.